Capacity Building in Public Sector Banks Through E-Learning - Jain, Vineet Kumar; Acharya, Asit Balwantrai (Indian Journal of Finance, 2025)
Purpose : This study examined infrastructure readiness for capacity building in public sector banks by analyzing the potential and requirements of e-learning. The primary aim of this study was to determine the factors that contribute to capacity building through the effective implementation of e-learning. Methodology : A large Indian public-sector bank was selected for this study. Data were gathered from more than five lakh e-learning courses completed by learners. Additional qualitative data were collected from focus group discussions. Quantitative analyses were conducted using descriptive statistics. Content analysis was also used to interpret learners’ comments. Findings : The study indicated that banks might face challenges in reaching their desired capacity without implementing an e-learning system. It was also observed that the availability of e-learning on mobile devices enhanced the learning potential of an organization. Role-based social learning platforms could contribute to effective learning outcomes. Practical Implications : Employees’ skills can be enhanced by investing in e-learning programs. Mobile learning access also contributes to achieving the desired results. The creation of engaging e-learning content and the introduction of incentives also contribute to capacity building. It is also recommended that role-specific certification resources and social learning be provided with support from peers and chatbots. Originality : The study examined the unique issue of capacity building in public sector banks in India. The objective was to establish a framework for capacity building that emphasized role-based learning, social learning platforms, and access to, as well as incentives for, e-learning.